Wolbachia affects mitochondrial population structure in two systems of closely related Palaearctic blue butterflies - Alena Sucháčková Bartoňová (Nature Portfolio, 2021)
Abstract The bacterium Wolbachia infects many insect species and spreads by diverse vertical and horizontal means. As co-inherited organisms, these bacteria often cause problems in mitochondrial phylogeny inference. The phylogenetic relationships of many closely related Palaearctic blue butterflies (Lepidoptera: Lycaenidae: Polyommatinae) are ambiguous. We considered the patterns of Wolbachia infection and mitochondrial diversity in two systems: Aricia agestis/Aricia artaxerxes and the Pseudophilotes baton species complex. We sampled butterflies across their distribution ranges and sequenced one butterfly mitochondrial gene and two Wolbachia genes. Both butterfly systems had uninfected and infected populations, and harboured several Wolbachia strains. Wolbachia was highly prevalent in A. artaxerxes and the host’s mitochondrial structure was shallow, in contrast to A. agestis. Similar bacterial alleles infected both Aricia species from nearby sites, pointing to a possible horizontal transfer. Mitochondrial history of the P. baton species complex mirrored its Wolbachia infection and not the taxonomical division. Pseudophilotes baton and P. vicrama formed a hybrid zone in Europe. Wolbachia could obscure mitochondrial history, but knowledge on the infection helps us to understand the observed patterns. Testing for Wolbachia should be routine in mitochondrial DNA studies.